2017
DOI: 10.1038/pr.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and ventilation decrease surface density of glomerular capillaries in lambs, regardless of postnatal respiratory support mode

Abstract: Background Prematurity is often complicated by respiratory support, including invasive mechanical ventilation (IMV) and non-invasive support (NIS). Compared to IMV, NIS reduces injury to the lung and brain. Prematurity may also disrupt glomerular architecture. Whether NIS differentially affects glomerular architecture is incompletely understood. We hypothesized that IMV would lead to greater disruption of glomerular architecture than NIS. Methods This is a secondary analysis of kidneys from moderately preter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Sutherland and Staub both used preterm sheep models with sheep born at 130 days of gestation (comparable to 35 weeks gestation in humans) [ 63 , 64 ]. Both studies found normal glomerular numbers, which can be explained by the gestational age by which nephrogenesis is complete.…”
Section: Vascular Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Sutherland and Staub both used preterm sheep models with sheep born at 130 days of gestation (comparable to 35 weeks gestation in humans) [ 63 , 64 ]. Both studies found normal glomerular numbers, which can be explained by the gestational age by which nephrogenesis is complete.…”
Section: Vascular Developmentmentioning
confidence: 99%
“…Sutherland described preterm animals to have a reduced glomerular capillary length, surface area, and total kidney filtration surface area [ 63 ]. Staub compared the effect of 3 and 21 days of mechanical ventilation [ 64 ]. After preterm birth, glomerular capillarization increased.…”
Section: Vascular Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Details of the perinatal steps were reported by our group previously (5,44,61,66,71). Briefly, the fetuses were exposed to antenatal steroids for 48 h before Cesarean section (exit procedure) delivery.…”
Section: Surgical Preparation and Management Of Preterm Lambs And Termentioning
confidence: 99%
“…The lambs were given Beuthanasia solution (0.25 ml/kg; Intervet, Madison, NJ) followed by potassium chloride (10 mEq; Hospira, Lake Forest, IL) intravenously. Terminal tissue collection has been reported by our group (5,44,61,66,71). Briefly, the entire left lung was insufflated with fixative and processed by systematic, uniform, random methods for quantitative histology (39).…”
Section: Terminal Studiesmentioning
confidence: 99%